Mechanisms and modulation of microvesicle uptake in a model of alveolar cell communication - Schneider, Daniel J.; Speth, Jennifer M.; Penke, Loka R.; Wettlaufer, Scott H.; Swanson, Joel A.; Peters-Golden, Marc (The Journal of biological chemistry, 2017)
Extracellular vesicles, including exosomes and shed microvesicles (MVs), can be internalized by recipient cells to modulate function. Although the mechanism by which extracellular vesicles are internalized is incompletely characterized, it is generally considered to involve endocytosis and an initial surface-binding event. Furthermore, modulation of uptake by microenvironmental factors is largely unstudied. Here, we used flow cytometry, confocal microscopy, and pharmacologic and molecular targeting to address these gaps in knowledge in a model of pulmonary alveolar cell-cell communication. Alveolar macrophage–derived MVs were fully internalized by alveolar epithelial cells in a time-, dose-, and temperature-dependent manner. Uptake was dependent on dynamin and actin polymerization. However, it was neither saturable nor dependent on clathrin or receptor binding. Internalization was enhanced by extracellular proteins but was inhibited by cigarette smoke extract via oxidative disruption of actin polymerization. We conclude that MV internalization occurs via a pathway more consistent with fluid-phase than receptor-dependent endocytosis and is subject to bidirectional modulation by relevant pathologic perturbations.